Understanding the heritability of heart rhythm and conduction disorders (2018)
The electrocardiogram (ECG) is a tool to obtain evidence for arrhythmias, which are related with cardiac conduction system abnormalities, myocardial ischemias and cardiac response to drugs. Additionally, ECG measurements are useful in prediction of the outcomes of patients with heart rythm disease, and prediction of cardiovascular mortality in healthy subjects.